Pendampingan Komunitas Laskar Belajar Omah Harsa untuk Meningkatkan Motivasi dan Minat Belajar, Potensi Enterpreneurship, dan Pola Hidup Sehat - Prayitno, Trio Ageng; Hidayati, Nuril; M, Mukarom; Jauharoh, Firda Eka (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P2M) IKIP Budi Utomo Malang, 2024)
The situation analysis shows that the motivation and interest in learning of Laskar Belajar Community Omah Harsa students is lacking, the students' entrepreneurial potential has not been developed, and the students' healthy lifestyle needs to be cultivated. Based on the agreement between the service team and partners, the Omah Harsa Community Learning Team's mentoring activities aim to increase students' motivation and interest in learning, entrepreneurship potential, and healthy lifestyles. The method of implementing service consists of observation, planning, implementation, and evaluation of activities. The place for service activities is the Omah Harsa Community Learning Army, Tanjungrejo Village, Sukun District, Malang City. The results of service activities show that student's motivation and interest in learning have increased by 71%, students' entrepreneurial potential has increased by 90%, and students' healthy lifestyles has increased by 85%. This service activity concludes that the service activity has a positive impact on the students of Laskar Belajar Community Omah Harsa in increasing motivation and interest in learning, entrepreneurial potential, and a healthy lifestyle.